Photo of Glastonbury Abbey taken by Elaine Steinbeck on her visit in the 1980s - Unknown:::photographer:::::::::::: (2024)
This photo of Glastonbury Abbey was taken by Elaine Steinbeck when she re-visited the area in 1980s. The Abbey was a monastery in Glastonbury, Somerset, England. From at least the 12th century, the Glastonbury area has been associated with the legend of King Arthur, a connection promoted by medieval monks who asserted that Glastonbury was Avalon. In 1191 the alleged discovery of King Arthur and Queen Guinevere's tomb in the cemetery added interest in the site. John and Elaine visited here in 1959 when Steinbeck was researching and writing The Acts of King Arthur and his Noble Knights.